2006
DOI: 10.2337/dc06-0751
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Intensive Insulin Therapy in Adults With Type 1 Diabetes and High Risk for Severe Hypoglycemia and Diabetic Ketoacidosis

Abstract: OBJECTIVE -Diabetes treatment and teaching programs (DTTPs) for type 1 diabetes, which teach flexible intensive insulin therapy to enable dietary freedom, have proven to be safe and effective in routine care. This study evaluates DTTP outcomes in patients at high risk for severe hypoglycemia and severe ketoacidosis.RESEARCH DESIGN AND METHODS -There were 96 diabetes centers that participated between 1992 and 2004. A total of 9,583 routine-care patients with type 1 diabetes were examined before and 1 year after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 24 publications
(20 reference statements)
5
22
0
Order By: Relevance
“…These data confirm earlier reports of a major reduction in severe hypoglycaemia 12 months after the ITTP and DAFNE 6, 10, 11, which is largely independent of HbA 1c (above or below 58 mmol/mol, 7.5%), insulin type or injection frequency. We propose the 76% reduced risk of severe hypoglycaemia arises from the total DAFNE education package, not just the basal insulin regimen.…”
Section: Discussionsupporting
confidence: 91%
“…These data confirm earlier reports of a major reduction in severe hypoglycaemia 12 months after the ITTP and DAFNE 6, 10, 11, which is largely independent of HbA 1c (above or below 58 mmol/mol, 7.5%), insulin type or injection frequency. We propose the 76% reduced risk of severe hypoglycaemia arises from the total DAFNE education package, not just the basal insulin regimen.…”
Section: Discussionsupporting
confidence: 91%
“…Five papers reporting three studies focused on T1DM, [251][252][253][254][255] eight focused on T2DM, [246][247][248][249][250]260,261,264 the remaining 15 included mixed populations. [237][238][239][240][241][242][243][244][245][256][257][258][259]262,263 Thirteen of the studies were conducted in the USA, [237][238][239][244][245][246][247][248][256][257][258][259]262 one in the UK, 240 three from Germany (in five papers), 251,[253][254][255]260 three from Austria, 250,…”
Section: Description Of the Studiesmentioning
confidence: 99%
“…Participating populations ranged from 85 to 9583 participants. One study in three papers, [253][254][255] reported a decade of data on nearly 10,000 patients involved in a national programme of inpatient self-management education to teach people with T1DM to adjust insulin dose according to expected food intake and pre-meal blood sugar.…”
Section: Description Of the Studiesmentioning
confidence: 99%
See 2 more Smart Citations